Diet quality and associations with motivation and ability to consume a healthy diet among adolescents from urban low-income households in Bangladesh - Akter, Mahsina Syeda; Snoek, Harriette M.; Rasheed, Sabrina; Maasen, Kim; Thilsted, Shakuntala H.; Feskens, Edith J.M.; Talsma, Elise F. (Elsevier, 2024)
In low- and middle-income countries, particularly in urban areas, adolescent diets consist mainly of energy-dense and nutrient-poor foods, putting them at risk of malnutrition and non-communicable diseases (NCD). In Bangladesh, little is known about the diet quality of adolescents, their food choices and the drivers of such choices. This study assessed motivations and ability to consume a healthy diet among adolescent girls and boys from low-income urban families and how these drivers were associated with dietary diversity and diet quality. A cross-sectional survey was conducted among 299 adolescents (15–19 years) from low-income households in Dhaka city during September–October 2020. The Diet Quality Questionnaire was used to collect non-quantitative food intake in the previous day or night to calculate diet quality indicators of food group diversity score, % of adolescents achieving minimum dietary diversity, NCD-Protect and NCD-Risk and the Global Dietary Recommendations score. Motivation was measured by 11 food choice motives. Ability was measured by belief in own ability to engage in healthy eating behaviors (self-efficacy). Adolescent diets showed a mean food group diversity of 4.9 out of 10, with 60% of adolescents achieving minimum dietary diversity, but lacked health-promoting foods (average of 2.7 out of 9 food groups) yet included few foods to avoid and limit (1.6 out of 9). Adolescents valued food choice motive ‘safety' the most, followed by ‘health', ‘taste', ‘price', ‘convenience' and ‘local or seasonal'. A higher motivation to consume ‘local or seasonal' and a lower motivation driven by ‘price', and a higher perceived self-efficacy were associated with better diet quality. Future interventions should address self-efficacy, concerns about food price and increase local and seasonal foods availability in the urban poor food environment of Dhaka to improve overall diet quality.